Pertumbuhan vegetatif Beras Upland (Oryza sativa L.) di Lahan Gambut dengan Menyediakan Ash Serbuk Gergaji dan Hijau Spesies Legum Pupuk - Gultom, Virnando Reville; Sjofjan, Jurnawaty; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to determine the gift effect of sawdust ash and green manure legume species against vegetative growth of upland rice in peatlands and get the best dose. The research was conducted at the experimental farm peat Faculty of Agriculture, University of Riau. This research was conducted on January to June 2013. The research was done by using Completely Randomized Block Design (CRBD) factorial 4 x 4, the first factor that is the dose of sawdust ash (0 ton/ha, 5 ton/ha, 7,5 ton/ha and 10 ton/ha) and the second factor the dose of green manure legume species (0 ton/ha, 5 ton/ha, 10 ton/ha, and 15 ton/ha). Data were analyzed by Analysis of Variance and then further tested by Duncans New Multiple Range Test (DNMRT) at the level of 5%. Visible indicator of treatment parameters plant height, plant dry weight, the maximum number of tillers, number of productive tillers, flag leaf length and age out panicles. The results showed ash sawdust giving 5 ton/ha to 10 ton/ha green manure legume species to increase vegetative growth of upland rice which give significantly different results for plant height, plant dry weight, number of tillers and the maximum length of the flag leaf. Keyword : upland rice, sawdust ash, green manure